Prarancangan Pabrik Aluminium Sulfat Dari Asam Sulfat Dan Kaolin Kapasitas 20.000 Ton Per Tahun - Nurtyasti, Warih (2016)
Aluminum Sulfate is commonly known as alum, can be used as a control pH of the water treatment, precipitating materials, adhesive paper and tanning animal skin by removing fats and oils contained in the skin. Within five years of aluminum sulphate has increased, especially in the export product, this signifies that the needs of Aluminium Sulphate is not only needed by the factories in the country, and even overseas factories need products Aluminium sulphate. Aluminium sulphate is obtained by reacting sulfuric acid and kaolin. The reaction occurs at a temperature of 90 ° C at a pressure of 1 atm. Aluminum sulfate products produced as much as 2525.252 kg / hour, to produce the products according to the calculation, the required raw materials as much sulfuric acid 3797.603 kg / h and kaolin as much as 1317.536 kg / hour. Process support unit (utility) covers the supply of cooling water 17161.093 kg / hour, the water to steam demand of 522.750 kg / hour produced from boilers with diesel fuel amounted to 148.730 L / h, water for sanitation amounted to 2059.260 kg / hour , Aluminum sulphate factory needs electricity amounted to 466.580 kW obtained from PLN and provided a generator set as a backup. Compressed air requirement of 30 m3 / h. The factory is planned to set up in Purwakarta, West Java in 2020 with a land area of 9,869 m2 and require employees 150 people. Aluminum sulphate factory uses fixed capital of USD 183 447 950 599 and working capital of Rp 25,465,339,428. From the economic analysis of this plant demonstrates profit before and after tax was Rp 64,353,544,264 and Rp 48,265,158,198. Return on Investment (ROI) before and after tax, 35.1% and 26.3%. Pay Out Time (POT) before and after taxes, for 2.22 years and 2.75 years. Break Even Point (BEP) amounted to 49.71%, Shut Down Point (SDP) amounted to 28.21%, Discounted Cash Flow (DCF) accounted for 40.83%. Feasibility analysis of the data it can be concluded that the plant is feasible to set.